Reader’s satisfaction level towards The Star printed newspaper / Normala Mohd Hassan - Mohd Hassan, Normala (Faculty of Business and Management, 2007)
In a past few years, printed media such as newspapers and magazines are the most familiar medium to contribute the information to consumers. Nowadays there are a lot of reading materials in Malaysia for the purpose of giving the information to the customers. The Star is one of the newspaper that constantly changing in order to meet the needs of the people and to prepare for challenges in the new millennium. The purpose of this study is to identify the readers' satisfaction level towards The Star printed newspaper. Otherwise this study wants to examine whether readers' satisfaction will influence a result of loyalty among The Star readers. In order to achieve high standard of excellences and compete with other competitors, it is important for Star Publications (M) Berhad to build a long-term relationship with the customers to make them loyal with the organization, and at the same time try to maintain the quality of The Star.